Pemberdayaan Guru SMA melalui Penyusunan Modul Ajar Literasi dan Numerasi Berbasis Web dan Aplikasi - Bayu Surindra; Rika Riwayatiningsih; Mochamad Muchson; Faridha Nadzirotur Rohmah; Fredo Ladona Alamsyah (Pusat Riset dan Inovasi Nasional, 2025)
Students' literacy and numeracy skills are an integral part of achieving success in learning, requiring cooperation in all aspects so that literacy and numeracy skills in schools can be optimally developed. This community service activity aims to empower partner high school teachers in developing and implementing technology-assisted literacy and numeracy-based teaching modules to improve student learning outcomes. The method used was the Participatory Action Model, which emphasized the active involvement of partner teachers in all stages. The program was implemented in four stages, namely socialization of process standards, training in teaching module development, assistance with classroom implementation, and reflection and evaluation. This activity was attended by 33 teachers from two partner high schools in Blitar City. The results of this activity were that the training produced 10 teaching modules covering 10 social studies elective subjects, which were documented in the school's application and website. At the implementation stage, 60% of teachers and 60% of students achieved the Learning Objective Achievement Criteria (KKTP), and after remedial activities and micro teaching, 100% of teachers and students successfully met the KKTP. These findings indicate that systematic assistance in the development and implementation of digital-based literacy and numeracy teaching modules can improve teacher competence and student learning outcomes. This activity needs to be carried out continuously to strengthen the culture of literacy and numeracy in partner schools.